Knowledge of family members on the rights of individuals affected by mental illness - Vania Moreno; Guilherme Correa Barbosa
The objective of this investigation was to understand what family members know about the rights of individuals affected by mental illness. To this end, a qualitative exploratory study was conducted. A semi-structured interview was used for data collection. Eighteen family members were interviewed at a psychosocial care center (CAPS) and a civil society organization (CSO) located in a municipality in the state of São Paulo, Brazil, between March and September 2013. Data were analyzed using thematic content analysis and the following categories were constructed: mental health services and the rights of individuals affected by mental illness. We were able to infer that in addition to drug-based therapy, mental health services must provide therapeutic activities. Family members of those affected by mental illness were unaware of the Brazilian Psychiatric Reform Law and mentioned the following rights: welfare benefits, free public transport, basic food basket and medications.